Current Progress on MicroRNA-Based Gene Delivery in the Treatment of Osteoporosis and Osteoporotic Fracture - Xi Sun; Qi Guo; Wenhua Wei; Stephen Robertson; Ying Yuan; Xianghang Luo (International Journal of Endocrinology)
Emerging evidence demonstrates that microRNAs, as important endogenous posttranscriptional regulators, are essential for bone remodeling and regeneration. Undoubtedly, microRNA-based gene therapies show great potential to become novel approaches against bone-related diseases, including osteoporosis and associated fractures. The major obstacles for continued advancement of microRNA-based therapies in clinical application include their poor in vivo stability, nonspecific biodistribution, and unwanted side effects. Appropriate chemical modifications and delivery vectors, which improve the biological performance and potency of microRNA-based drugs, hold the key to translating miRNA technologies into clinical practice. Thus, this review summarizes the current attempts and existing deficiencies of chemical modifications and delivery systems applied in microRNA-based therapies for osteoporosis and osteoporotic fractures to inform further explorations.